Remote monitoring of the atmosphere in Ukraine during the COVID-19 restrictions - Lyalko, Vadim; Yelistratova, Lesia; Аpostolov, Aleksandr; Romanciuc, Inna (Scientific Centre for Aerospace Research of the Earth Institute of Geological Science National Academy of Sciences of Ukraine, Kyiv, Ukraine, 2020)
In March, 2020 World Health Organization declared COVID-19 a pandemic phenomenon. Beginning from the March, 12 2020 the quarantine restrictions have been introduced in Ukraine. The measures of global quarantine reducing industrial production and transportation have not led to the reduction in fluctuations of greenhouse gases. This study was dedicated to reveal distributions of CO2 and NO2 gases in the atmosphere for Ukraine. The gases were detected using the remote sensing data. The results show that NO2 emissions have been reduced during the quarantine restrictions accompanied by declining industry and transport activity. It is not significant decrease in CO2 content in the atmosphere, as it depends on both anthropogenic and natural factors.